Estudo epidemiológico de 261 dentes permanentes avulsionados de pacientes tratados em um serviço de urgência odontológica - GUEDES, Orlando Aguirre (2012)
Aim: To evaluate epidemiological aspects and clinical factors of avulsion of the permanent teeth. Material and Methods: The sample was composed by 170 patients (261 avulsed teeth) treated in Dental Urgency Service of the Dental School of the Federal University of Goiás, Brazil, between 2000 and 2008. The following informations were collected from the patients´ files: gender, age, cause of tooth avulsion, seasonal distribution, type and number of avulsed teeth, replantation, stage of root development, transport media, extra-oral period, presence of additional damage, treatment provided and post-traumatic complications. The statistical treatment analyzed data from frequency distribution and chi-square test. The level of significance was set at 5% for all analyses. Results: Higher occurrence of tooth avulsion was observed in males (71.18%) and patients with 6-10 and 11-15 years old (30.59% each one). The main etiologic factors involved were falls (51.76%), traffic accidents (29.41%) and violence (6.47%). The seasonal distribution showed that most cases occurred in Autumn (March to June; 31.18%), followed by Winter (June to September; 27.65%). The most affected tooth was the upper central incisor (62.45%), followed by the upper lateral incisor (21.46%). Significant proportion (67.23%) of traumatized teeth presented root apex completely formed. One hundred and nineteen teeth (45.59%) were replanted. The majority of the replanted teeth (89.08%) received delayed replantation. Thirty eight teeth (31.93%) were stored in dry media. Periodontal healing was observed in 41 teeth (34.45%), inflammatory root resorption in 44 teeth (36.97%) and replacement root resorption in 22 teeth (18.49%). The most frequent modalities of treatment for replanted teeth were endodontic treatment and the temporary filling of the root canal with calcium hydroxide (58.82%) and endodontic treatment and the definitive root canal filling (26.89%). Conclusion: There was a high number of dental avulsions in males, aged under 15 years, from falls and mainly involving maxillary anterior teeth, and low rate of replantation accompanied by a significant number of teeth stored in non-physiological over a long period time.